MEMOTRET WAJAH PENDIDIKAN SEKSUALITAS DI PESANTREN - Mahmudah, Nur (Pascasarjana IAIN Kudus, 2015)
Sexuality education oftenly understood in a wrong way as a deviant sexual behavior cause, whereas sexuality education aims to provide awareness of identity, relationships with others, reproductive health and responsible sexual behavior. Islam provides many materials in the socialization of the values of sexuality education. While Pesantren is an educational institution for the deepening religious understanding, it is necessary to study the practice of sexuality education in Pesantren. This article outlines descriptive teaching materials used in Pesantren. In conclusion, Pesantren indicates the new direction in the selection of new teaching materials in sexuality education.